Epithelial-Mesenchymal transition induces podocalyxin to promote extravasation via ezrin signaling - Fröse, Julia; Chen, Michelle B.; Hebron, Katie E.; Reinhardt, Ferenc; Hajal, Cynthia; Zijlstra, Andries; Kamm, Roger D.; Weinberg, Robert A. (Cell reports, 2018)
The epithelial-mesenchymal transition (EMT) endows carcinoma cells with traits needed to complete many of the steps leading to metastasis formation, but its contributions specifically to the late step of extravasation remain understudied. We find that breast cancer cells that have undergone an EMT extravasate more efficiently from blood vessels both in vitro and in vivo. Analysis of gene expression changes associated with the EMT program led to the identification of an EMT-induced cell-surface protein, podocalyxin (PODXL), as a key mediator of extravasation in mesenchymal breast and pancreatic carcinoma cells. PODXL promotes extravasation through direct interaction of its intracellular domain with the cytoskeletal linker protein ezrin. Ezrin proceeds to establish dorsal cortical polarity, enabling the transition of cancer cells from a non-polarized, rounded cell morphology to an invasive extravasation-competent shape. Hence, the EMT program can directly enhance the efficiency of extravasation and subsequent metastasis formation through a PODXL-ezrin signaling axis.
Gesehen am 28.04.2020